Conditions of Sustainable Development for Sme Entities in the Course of COVID-19 Pandemic - N. S. Mrochkovskiy (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
A number of international organizations have published recently the forecasts concerning aspects of economic impact exerted by corona-virus pandemic. In July update of economic outlook for 2020 the IMF forecast a drop in global GDP by 4.9% in 2020, which is lower by 1.9 per cent point in comparison with the April forecast, which will be followed by partial restoration and growth by 5.4% in 2021. The report on global investment for July 2020 shows a downfall in global foreign investment to 40% in 2020 and later its further decline by 10% in 2021. MOT estimates the COVID-19 impact, which will cause an increase in global unemployment by 5.3 m (a low scenario) and 24.7 m (a high scenario). It proves that support of business activity will be especially difficult for small and medium enterprises. The article shows how COVID-19 pandemic influences entities of small and medium entrepreneurship (SME) and demonstrates first evidences and estimations of its impact. It also provides a list of political steps aimed at raising SME sustainability in 60 countries. Taking into account the fact that the situation is changing very fast, the review of possible steps is not exhaustive, in some cases it includes political measures only planned for implementation that are being still discussed or considered. The latest surveys of enterprises showed a certain improvement of the situation connected with serious political efforts aimed at elimination of liquidity deficit at small and medium enterprises and suspension of local restrictions in some countries. In this context political perspective is slowly shifting from measures of supporting liquidity for SME entities, which are still a priority in the majority of countries, to measures of supporting restoration.